Implementasi Pembelajaran Masa Pandemi dan Implikasinya terhadap Minat Belajar Pendidikan Agama Islam - Masnia, Risa (Kartika: Jurnal Studi Keislaman, 2025)
Based on the demands placed on educators to create interactive learning experiences that can enhance students' learning interest. This study aims to analyze the implementation of learning during the pandemic period and its implications for students’ interest in learning Islamic Religious Education. A quantitative approach was employed, involving a population of 202 students and a randomly selected sample of 66 respondents. Data were collected through questionnaires, with instrument validity and reliability tests conducted to ensure accuracy. The data were analyzed using Pearson’s product-moment correlation, t-test, and coefficient of determination analysis. The findings indicate that the calculated t-value is less than the critical t-value (0.240 < 1.668), implying that the null hypothesis is accepted and there is no statistically significant effect of learning implementation on learning interest. However, the significance value of 0.000 < 0.05 indicates a strong correlation between the variables. The coefficient of determination is 0.640, suggesting that the implementation of learning during the pandemic contributes 64% to the variation in students’ interest in learning Islamic Religious Education, which is categorized as a strong relationship.